2000
DOI: 10.1002/1529-0131(200001)43:1<175::aid-anr22>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Disease-modifying activity of SB 242235, a selective inhibitor of p38 mitogen-activated protein kinase, in rat adjuvant-induced arthritis

Abstract: Objective. To evaluate the effects of SB 242235, a potent and selective inhibitor of p38 mitogen-activated protein (MAP) kinase, on joint integrity in rats with adjuvant-induced arthritis (AIA).Methods. Male Lewis rats with AIA were orally treated either prophylactically (days 0-20) or therapeutically (days 10-20) with SB 242235. Efficacy was determined by measurements of paw inflammation, dualenergy x-ray absorptiometry for bone mineral density (BMD), magnetic resonance imaging (MRI), microcomputed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
121
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(123 citation statements)
references
References 31 publications
(40 reference statements)
1
121
0
1
Order By: Relevance
“…High levels of activated MKKs were confirmed by Western blot analysis, with increases in both phospho-MKK3 and -MKK6. Because p38 activation contributes to bone destruction and synovial inflammation in animal models of arthritis, 37 one can infer that similar pathways might be relevant in RA. If so, MKK3 and MKK6 are potential gateways to p38 activation in rheumatoid synovium and could enhance cytokine and protease production.…”
Section: Discussionmentioning
confidence: 70%
“…High levels of activated MKKs were confirmed by Western blot analysis, with increases in both phospho-MKK3 and -MKK6. Because p38 activation contributes to bone destruction and synovial inflammation in animal models of arthritis, 37 one can infer that similar pathways might be relevant in RA. If so, MKK3 and MKK6 are potential gateways to p38 activation in rheumatoid synovium and could enhance cytokine and protease production.…”
Section: Discussionmentioning
confidence: 70%
“…This finding suggests potential therapeutic targets for combating PGE 2 -related inflammation in cartilage, most notably, ERK-1/2 and p38 MAPKs. MAPK activation may be involved in inflammatory and degenerative arthropathies (44,45), and several therapeutic trials have indicated that p38 MAPK inhibitors can halt joint disease (46)(47)(48). However, the use of MAPK inhibitors in clinical practice is limited by the ability of these compounds to block overall MAPK activity.…”
Section: Discussionmentioning
confidence: 83%
“…Our examination of p38 MAPK distribution in developing limbs revealed the presence of cells expressing constitutively active p38 MAPK at sites of joint cavity formation and is endorsed by our demonstration that cultured cells derived from these sites also conserve p38 MAPK in the active state. Increasing emphasis on use of p38 MAPK inhibitors as anti-inflammatory therapies for joint disorders may therefore require re-evaluation (38). Our findings show that p38 MAPK regulates mechanically induced changes in extracellular matrix formation and, therefore, have implications for use of p38 MAPK-targeted antiinflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%